RADIOACTIVE SAND & LOW-RESISTIVITY OIL SANDS IN A 3D SEISMIC-GEOLOGICAL FACIES MODEL OF DETA FIELD, TERMIT BASIN, NIGER. - CHANG , EE VON (2018)
Deta Field (pseudo name) located in the South-West area of Dinga Trough, Termit Basin. The total study surface area of Deta Field covered by 3D seismic is about 945. It is a hydrocarbon producing field with NW-SE faulting elongated anticlinal structure. The major reservoir in Deta Field is the Sokor formation which is divided into six zones with interbedded sand: E0, E1, E2, E3, E4 and E5. The thickness of each sand ranges from 80-140 meters.